Clinical features and outcomes of patients with stable or unstable chest pain and no-obstructive coronary artery disease - Cambise, Nello; Telesca, Alessandro; Tremamunno, Saverio; Felici, Tamara; De Vita, Antonio; Filice, Monica; Ingrasciotta, Gessica; Ruscio, Eleonora; Crea, Filippo; Lanza, Gaetano A. (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary microvascular dysfunction can be responsible for both stable angina and acute coronary syndrome (ACS). There are scarce data, however, about comparisons of clinical characteristics and outcomes of these 2 groups of patients. Materials and methods We studied 47 consecutive patients who underwent coronary angiography for angina syndromes and showed no obstructive stenosis. Patients were divided in 2 groups, according to their clinical presentation, i.e., stable angina (n = 21) or non-ST segment elevation ACS (NSTE-ACS; n = 26). An intracoronary acetylcholine (Ach) test was performed in 12 and 17 patients of the 2 groups, respectively. Angina status, assessed by Seattle Angina Questionnaire (SAQ), and clinical events were assessed after 1, 6, and 30 months. An exercise stress test was performed 1 month after discharge. Results Clinical characteristics and exercise test results of the 2 groups were largely similar. Ach testing induced epicardial or microvascular spasm in 6 (50.0%) and 10 (58.8%) stable and NSTE-ACS patients, respectively (p = 0.72). Stable patients reported higher rates of angina, compared to NSTE-ACS patients, both at 1 (p = 0.04) and 30 months (81 vs. 50%, p = 0.036) of follow-up. SAQ scores were also lower in stable vs. NSTE-ACS patients. Ach testing results showed no association with clinical outcomes. Conclusion Clinical characteristics and exercise and Ach testing results are similar in angina patients with no-obstructive coronary artery disease with a stable or NSTE-ACS presentation. Stable patients show a worse symptomatic outcome irrespective of Ach test results.